Evaluation of Self-Differentiation and Awareness of Creativity for the Players of the University of Kufa Basketball Team - Abed Al-Gburi, Dr. Ayman Hani (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to identify the following: • Identify the differentiation of self and awareness of creativity for the players of the University of Kufa basketball team. • Assessment of self-differentiation and awareness of creativity for the players of the University of Kufa basketball team. The researchers used the descriptive method in the survey method, and the research community determined the players of the team of the University of Kufa basketball and the number (12) players, and then the researchers selected and applied the criteria of self-differentiation and awareness of creativity on the research sample, the results were extracted and the use of appropriate statistical treatments to reach the results The results were presented, analyzed and discussed. The researchers reached the most important conclusions: • The players of the University of Kufa basketball team enjoy a high level of self-differentiation and awareness of creativity. • There are real differences when the players of the University of Kufa basketball in the differentiation of self and awareness of creativity.